The state of nephrology in South Asia - Jha, V; Ur-Rashid, H; Kumar Agarwal, S; Fazal Akhtar, S; Kumar Kafle, R; Sheriff, R; Board, I (Elsevier, 2018)
The South Asia region of the International Society of Nephrology comprises 8 countries (Table 1) with a combined population of 1.77 billion, about 29% of world population in 2016. The World Bank classifies Afghanistan and Nepal as low-income countries; Bangladesh, Bhutan, India, Pakistan, and Sri Lanka as low-middle-income countries, and the Maldives as an upper middle-income country. Over 65% of the population in the region lives in rural areas.